SURGICAL MANAGEMENT OF A COMPLETE FRACTURE IN A PARROT.-A CASE REPORT. - Shukla, B P; Ahmad, Rayees; Ali, Rameez; Arya , Pooja (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A Case of simple complete transverse fracture of tibiotarsus bone in a parrot was brought to clinic and managed successfully.
Keywords: Parrot; Tibiotarsus; Ketamine